Peningkatan resiliensi penyintas pelecehan seksual melalui terapi pemaafan - Eukaristianica Theofani; Ike Herdiana (Jurnal Ilmiah Psikologi Terapan, 2020)
Objectives: An unwanted pregnancy due to sexual abuse feels so heavy for a woman so that it needs the ability to rise from adversity called resilience. Resilient individuals are able to deal with pressures in their lives and try to deal with stress through coping strategies, which is to forgive. The purpose of this study was to determine the increase in resilience in women survivors of sexual abuse who experienced an unwanted pregnancy through forgiveness therapy.Method: This research uses quasi-experimental method with A-B reversal design. Subjects were 3 survivors of sexual abuse who experienced an unwanted pregnancy with low or moderate resilience based on the CYRM-28 scale categorization. Data were analyzed by Wilcoxon visual analysis and nonparametric analysis.Findings: The results of visual analysis showed an increase in resilience, while the results of the nonparametric analysis showed a non-significant difference in resilience (0.109> 0.05) between before and after the intervention was given. Even so, measurement of effect size shows that forgiveness therapy has a big effect (0.926> 0.8) to increase the resilience of survivors of sexual abuse who experienced an unwanted pregnancy.Conclusions: the research hypothesis was rejected.It means there was no effect of the application of forgiveness therapy to increase resilience in women survivors of sexual harassment who experienced an unwanted pregnancy.